DESKRIPSI KESULITAN BELAJAR KIMIA PADA MATERI ASAM BASA DALAM PEMBELAJARAN INTERAKTIF - Anelka, Virginia Putri; Fitri, Bali Yana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia, 2025)
The teaching of acid-base material has been carried out using interactive learning strategies, but students still experience learning difficulties. This study aims to describe the learning difficulties and reveal the factors causing learning difficulties experienced by students in acid-base material in interactive learning. The type of research is descriptive with a qualitative approach. The study was conducted through the analysis of daily assessment data, the distribution of questionnaires, and interviews with teachers and students to identify the factors causing learning difficulties. The results of the daily assessment analysis showed that the majority of students in class XI-F1 experienced difficulties in learning acid-base material. The level of difficulty was classified as not difficult (8.8%), slightly difficult (14.7%), moderately difficult (38.2%), difficult (32.3%), and very difficult (5.9%). Meanwhile, internal factors causing learning difficulties include physical factors (71.3%), interest (71.6%), talent (58.9%), motivation (65.6%), and study habits (81.9%). As for external factors, they include teaching methods (72.9%), study time (60.3%), school facilities (72.9%), family environment (68%), and social environment (68.4%). The results of this study are expected to prevent similar learning difficulties by considering students' talents and study time. ABSTRAKPembelajaran materi asam basa telah dilakukan dengan strategi pembelajaran interaktif, tetapi kesulitan belajar tetap dialami oleh peserta didik. Penelitian ini bertujuan untuk mendeskripsikan kesulitan belajar dan mengungkapkan faktor penyebab kesulitan belajar yang dialami oleh peserta didik pada materi asam basa dalam pembelajaran interaktif. Jenis penelitian ini adalah deskriptif dengan pendekatan kualitatif. Studi ini dilakukan dengan analisis data penilaian harian, pemberian angket, dan wawancara guru juga peserta didik untuk mengetahui faktor penyebab kesulitan belajar. Hasil analisis penilaian harian menunjukkan mayoritas peserta didik kelas XI-F1 mengalami kesulitan dalam mempelajari materi asam basa. Dengan tingkat kesulitan tergolong tidak sulit dengan persentase sebesar 8,8%, sedikit sulit dengan persentase 14,7%, cukup sulit dengan persentase sebesar 38,2%, tergolong sulit dengan persentase sebesar 32,3%, dan sangat sulit sebanyak 5,9%. Sementara itu, faktor internal penyebab kesulitan belajar berupa fisik (71,3%), minat (71,6%), bakat (58,9%), motivasi (65,6%), dan kebiasaan belajar (81,9%). Sedangkan untuk faktor eksternal ada cara mengajar guru (72,9%), waktu belajar (60,3%), fasilitas sekolah (72,9%), lingkugan keluarga (68%), dan lingkungan sosial (68,4). Hasil penelitian ini diharapkan dapat mencegah kesulitan belajar serupa dengan mempertimbangkan bakat dan waktu belajar peserta didik.